Chironomid-inferred summer temperature development during the late Rissian glacial, Eemian interglacial and earliest Würmian glacial at Füramoos, southern Germany - Bolland, Alexander; Kern, Oliver A.; Koutsodendris, Andreas; Pross, Jörg; Heiri, Oliver (Boreas, 2021)
Eemian pollen records from central Europe describe a transition from thermophilous tree taxa in the early Eemian to boreal tree taxa in the late Eemian with forest opening in the subsequent stadial. Available summer-temperature reconstructions for the mid- to late Eemian transition show decreasing values during that time. We present a new chironomid record from southern Germany that covers the mid-Eemian to the end of the first Würmian stadial (c. 125-105 ka) and also parts of the late Rissian glaciation and early Brörup interstadial of the early Würmian glaciation. Based on this record we describe lake development in the former Füramoos palaeolake and quantitatively reconstruct July air temperature during the examined interval. Late Rissian sediments are dominated by two chironomid taxa, Sergentia coracina-type and Micropsectra radialis-type, indicating very cold conditions. Following an uncertain interval, probably including a hiatus at the late Rissian/Eemian transition, mid-Eemian sediments contain Tanytarsus glabrescens-type and Tanytarsus mendax-type suggesting relatively high July air temperatures. During the late Eemian, typically thermophilic taxa such as Tanytarsus glabrescens-type disappear, suggesting decreasing temperatures. Stadial A is associated with increases in Microtendipes pedellus-type suggesting more oligotrophic conditions. Early Brörup sediments contain Tanytarsus glabrescens-type, suggesting a slight increase in July air temperature. Reconstructed July air temperatures show temperatures of 7-8 °C during the late Rissian and a decline from ˜15.5-12 °C during the mid- to late Eemian associated with decreasing Northern Hemisphere July insolation. July air temperature values vary between 12 and 14 °C in the late Eemian, while reconstructed temperatures remain within 12-13.5 °C during Stadial A. Our new chironomid-based temperature reconstruction provides valuable corroboration and new quantification of temperature development from the mid-Eemian to the early Brörup interstadial as well as for sections of the late Rissian from the alpine foreland of southern Germany.